2019
DOI: 10.1111/eje.12439
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical dental training: Association between difficulty in performing restorative procedures and the adoption of ergonomic posture

Abstract: Objective:The aim of this study was to determine any correlations between difficulty in performing restorative procedures and the adoption of ergonomic posture by dental students in a preclinical course. Methods:The sample was composed of second-year undergraduate students enrolled in the School of Dentistry of São Paulo State University (UNESP), Araraquara (n = 56). The data were collected from weekly records in which students who had participated in training in a preclinical restorative dentistry laboratory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 15 publications
0
7
0
1
Order By: Relevance
“…Additionally, static positions are often riskier for the musculoskeletal system than dynamic movements in dentistry. Neves et al [ 32 ] found a significant correlation between the students’ difficulties in preclinical restorative procedures and their difficulties in maintaining an ergonomic posture. The results of a study by Diaz-Gaballero et al [ 7 ] showed that exaggerated body flexion or cervical torsion, performed to improve the view of the oral cavity, caused musculoskeletal pain among Colombian dental students.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, static positions are often riskier for the musculoskeletal system than dynamic movements in dentistry. Neves et al [ 32 ] found a significant correlation between the students’ difficulties in preclinical restorative procedures and their difficulties in maintaining an ergonomic posture. The results of a study by Diaz-Gaballero et al [ 7 ] showed that exaggerated body flexion or cervical torsion, performed to improve the view of the oral cavity, caused musculoskeletal pain among Colombian dental students.…”
Section: Introductionmentioning
confidence: 99%
“…En Brasil, un estudio llevado a cabo con 56 estudiantes que analizó el efecto del entrenamiento preclínico, constató mediante registros semanales utilizando una escala numérica análoga, una correlación entre la dificultad en realizar las maniobras preclínicas y las dificultades en adoptar en ellas, posturas ergonómicas. Asimismo se constató que la percepción de los estudiantes sobre la dificultad en implementar posturas ergonómicas disminuía con el correr de los días en el programa de entrena-miento (p<0.001) (37).…”
Section: Conclusionesunclassified
“…12,13 When preclinical training in restorative dentistry begins, many students do not have enough manual dexterity and self-confidence to face the first obstacles that arise in practical learning, which can result in difficulties in performing both preclinical procedures 10 and in adoption of ergonomic work postures. 14 The development of manual dexterity is essential for the practice of dentistry. However, if this process is not properly conducted, it may compromise the student's self-confidence and consequently his/her preclinical and clinical learning.…”
Section: Introductionmentioning
confidence: 99%
“…2 Thus, although the development of new motor skills may take time in the beginning, it is important that this occurs gradually and properly, under specialized professional guidance. 2,14,15 According to Duong et al (2010), 2 after the development of manual dexterity, operators master their notion of space, force and positioning while holding the instruments. Therefore, it is possible that the learning of clinical skills after this phase of fine motor development allows students to be concerned only with the new skill being learned, optimizing their learning process and application of ergonomic concepts.…”
Section: Introductionmentioning
confidence: 99%